The Obstacles in Applying Electronic Commerce in Distributive Cooperatives in Tehran Province - M.M Alamdar Meybodi; V.R Mirabi; J Mohammadgholinia (تعاون و کشاورزی, 2011)
In the world today, e-commerce is known as a major comparative advantage for many companies. Considering the administration of the Fifth National Development Plan and the Policies of Article 44 of Constitution, which allocates a share of 25 percent for cooperation sector in the national economy, and considering the fact that distributive cooperatives constitute a significant portion of companies in Iran, identifying problems and obstacles in applying e-commerce in such organizations would be of great importance. Therefore, this study aims to investigate these obstacles in distributive cooperatives in Tehran Province. The current study was carried out with the purpose of investigating the obstacles to apply e-commerce in distributive cooperatives in Tehran province in 2010. The research type is applied, quantitative and retrospective. Questionnaires were used to gather data. Total number of distributive cooperatives in Tehran is 4000. Directing managers or one of the members of the board of directors were selected as the population of study, and by applying the Cochran formula the appropriate sample size was determined to be 187. Results show that financial deficits, technical problems, and behavioral-cultural barriers were the most important “Internal obstacles” and lack of necessary capabilities in business partners, lack of adequate competition in the market and lack of interest in customers were the most important “external obstacles” in applying e-commerce in distributive cooperatives in Tehran province.